Sectorial Analysis of the Fibrous Matrix of Vocal Folds in the Elderly - Pessin, Adriana Bueno Benito [UNESP] (2020)
Objective: to determine the sectorial concentration of fibrous matrix along the vocal folds of the elderly. Methods: Thirteen fresh vocal folds were removed from 13 cadavers. The subjects were divided into two groups: control group (CG) – age range 25–40 years (n = 5), and elderly group (EG), aged ≥70 years (n-8). The vocal folds were separated according to regions in: anterior macula flava (AMF), posterior macula flava (PMF), medial region (M) and lateral region of the membranous vocal fold (L). The material was examined using a scanning electron microscope and 10 pictures per region were obtained at 1200x magnification. The area of fibrous matrix was quantified in both groups using the AVSOFT Biovew Program. Results: Percentage (%) of fibrous matrix per region (%): AMF (EG = 86.78%; CG = 81.63%); PMF (EG = 88.19%; CG = 81.52%); M (EG = 84.92%; CG = 77.96%); L (EG = 83.93%; CG = 78.91%). Irregular distribution of a dense fibrous matrix was also more evident in the elderly's larynges in a qualitative assessments. Conclusion: A higher concentration of fibrous matrix was observed in the vocal folds of the elderly when compared to the control at all the studied regions. The greatest increase in the concentration of fibers in the medial portion of the body of the vocal folds is probably due to the phonatory stimulation. The macula flava remains functional even in the senile larynx.